2014
DOI: 10.1016/j.neuroscience.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Administration of S-methyl-l-thiocitrulline protects against brain injuries after intracerebral hemorrhage

Abstract: Although intracerebral hemorrhage (ICH) increases the level of glutamate in the perihematomal area and cerebral spinal fluid (CSF) in the ICH acute phase, it is unclear whether elevated glutamate activates neuronal nitric oxide synthase (nNOS) in the ICH brain and whether nNOS is an important target for ICH treatment. Here, we assessed the role of the nNOS inhibitor S-methyl-L-thiocitrulline (SMTC) in the activity of nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d) and ICH-induced brain injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Other investigators detected NOS overexpression and suggested the role of the NOS/NO/ONOO − pathway in BBB disruption using the Hb-injection rat model [ 10 , 43 ]. In contrast, administering nNOS inhibitor after ICH was found to protect BBB integrity and decrease both neuronal death and neurological deficits [ 74 ]. Moreover, iNOS knockout mice present significantly less brain edema after collagenase-induced ICH [ 75 ].…”
Section: Prooxidase In Ichmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators detected NOS overexpression and suggested the role of the NOS/NO/ONOO − pathway in BBB disruption using the Hb-injection rat model [ 10 , 43 ]. In contrast, administering nNOS inhibitor after ICH was found to protect BBB integrity and decrease both neuronal death and neurological deficits [ 74 ]. Moreover, iNOS knockout mice present significantly less brain edema after collagenase-induced ICH [ 75 ].…”
Section: Prooxidase In Ichmentioning
confidence: 99%
“…Hemin also activates the NF- κ B transcription factor via an undefined mechanism [ 77 , 78 ]. In addition, high levels of glutamate activate NOS through the NMDA receptor with subsequent Ca 2+ influx by phosphorylating IKB and NF- κ B translocation [ 74 , 79 ].…”
Section: Prooxidase In Ichmentioning
confidence: 99%
“…The activity of NOX enzymes increased significantly in hypertensive mice with spontaneous ICH [ 78 ]. A study also reported that activity of NADPH-d increased significantly in the rat striatum after ICH [ 79 ]. However, another study found that treatment with apocynin did not ameliorate the outcome of rats after ICH.…”
Section: Nox Enzymes In Cns Ischemic and Hemorrhagic Strokementioning
confidence: 99%